The reconstruction of the library of Francesco Maria II Della Rovere: studies and research, reorganisation and state of the holdings. A project and a conference to relaunch it - Fiammetta Sabba (Bibliothecae.it)
The contribution offers an historical-bibliographical overview of the library of Francesco Maria II Della Rovere and traces the studies conducted on it since the the project Il progetto di ricostruzione della ‘libraria’ di Francesco Maria II, born between 2007 and 2008, to arrive at 2023, when at the Conference La ricostruzione della biblioteca di Francesco Maria II Della Rovere. Studi e ricerche, riordino e stato dei fondi held at the Department of Cultural Heritage in Ravenna were illustrated the results achieved over the years.